2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34577
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Teamwork Skills Through an Engineering Service-learning Collaboration

Abstract: Her main areas of research interest are collaborative work-structures, virtual teams and team decision-making and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Though the SLSCs were aimed at the tribal students to spark an interest in science, this brought out an added benefit of building 21st century skills among the student mentors. Service learning initiatives develop skills, such as cross-cultural understanding, collaboration, communication, and writing, as already reported in the literature. , When asked for a self-report on the skills gained through the SLSC, the student mentors responded as shown in Table . The SLSCs have created a marked improvement in the collaboration and adaptability among postgraduate students.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Though the SLSCs were aimed at the tribal students to spark an interest in science, this brought out an added benefit of building 21st century skills among the student mentors. Service learning initiatives develop skills, such as cross-cultural understanding, collaboration, communication, and writing, as already reported in the literature. , When asked for a self-report on the skills gained through the SLSC, the student mentors responded as shown in Table . The SLSCs have created a marked improvement in the collaboration and adaptability among postgraduate students.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This accelerates the project timeline, saving time and resources compared to individual efforts. (Chowdhury & Murzi, 2019;Kozlowski, 2018;Pazos et al, 2020) Risk Mitigation Collaborative teamwork ensures that multiple experts review and validate designs, reducing the likelihood of errors or oversights that might lead to costly mistakes down the line. (Baker, Day, & Salas, 2006;Salas, Bisbey, Traylor, & Rosen, 2020…”
Section: Rationale Sourcesmentioning
confidence: 99%
“…Several previous studies have investigated the impact of task characteristics as an effective means of communication between members involved in group work. For example, Pazos et al (2020) highlighted the potential of increasing individual attraction to the task in keeping the team on track to achieve their goals. The literature showed that task attraction can directly influence users' parasocial interaction (Zheng et al, 2020), which may contribute to individual engagement (Coulson et al, 2012).…”
Section: The Mediating Role Of Task Attractionmentioning
confidence: 99%